Comparison of different universal adhesives’ bond strength to laser-assisted bleached enamel - Fatma Dilsad Oz; Ayşe Rüya Yazıcı; Cansu Atalay (Selcuk Dental Journal)
Objective: The aim of this in vitro study was to evaluate the bond strength of several universal adhesives used in different application modes to laser-assisted bleached enamel.Materials and Methods: Freshly extracted 72 sound bovine incisors were used for the study. The teeth were bleached with 38% of hydrogen peroxide gel that was activated with a diode laser (Epic). The diode laser with a 949nm wavelength was used at 7 W in continuous mode for 30 s. After bleaching procedure, the teeth were kept in artificial saliva for 2 weeks. The bleached teeth were randomly assigned into three groups according to different universal adhesive systems (n=24); Single Bond Universal-SU, All-Bond Universal-ABU and Adhese Universal-ADU. All adhesives were applied in two modes: a- etch&rinse (ER); and b- self etch (SE). A cylinder-shaped resin composite was placed on treated surfaces and cured. After storage of specimen in distilled water for 24 h, they were subjected to shear bond strength test. Data were analyzed using two-way ANOVA followed by Bonferroni test (α = 0.05) Results: The highest mean shear bond strength values were obtained in Single Bond Universal group used in self-etch mode (p<0.05). No difference was observed between All-Bond Universal and Adhese Universal. In etch&rinse application mode, Adhese Universal resulted in significantly lower bond strength values (p<0.05) than Single Bond Universal and All-Bond Universal. For all groups, etch&rinse application mode caused significantly higher bond strength values.